A scoping review of wellbeing and quality of life among oil palm smallholders - Nur Hafizah Yusoff,; Er, Ah Choy; Noordeyana Tambi,; Azlan Abas, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Palm oil has been recognized as large world trade of vegetable oil around the globe. The vast improvement of planting palm trees and the numbers of oil palm export shown that these agricultural has huge potential for the farmers. The Objective of this paper is to evaluate the wellbeing and quality of life among oil palm smallholders. Since this is a review paper, a secondary data through various past researches has been collected and the data were extracted, and thematic analysis was used to organize the data. There is no denying that oil palm smallholders have received many benefits through their participation in palm plantations. Their economic wellbeing concludes having enough enough salary and job opportunities whereas psychology wellbeing includes being diligence, enthusiasm, not giving up, confident and honesty in the work done. They are also willing to take a risk in their plantation activity. The ssocial wellbeing of smallholders is the provision of roads, bridges, community centers, health and education services and communication infrastructure. All these aspects of wellbeing will lead to the enhancement the quality of life among the smallholders. Although there are several type of researches that has been conducted on social benefits from oil plantation but the numbers of researches still not adequate. Therefore, more research on the wellbeing and quality of life of oil palm smallholders need to be conducted.